Correlation of Vitamin D with Ferritin in Pregnant Mothers Chronic Energy Deficiency of the Second Trimester - Hendera Henderi; Salmon Charles P T Siahaan; Irwin Priyatna Kusumah; Heru Cahjono; Ferdinand A Tannus; Nimas Pristiwanto D S; Helen Octavia (Berkala Kedokteran, 2021)
Abstract: Based on the prevalence of the Kediri Health Office in 2013 and 2014, pregnancy in CED in Kediri was 6.6% and 6.7%, which was an increase of 0.1% from the previous year. According to the prevalence of CED pregnancy in Badas Puskesmas in 2013 and 2014, it was 7.8% and 6.1%. Aimed at knowing the differences in vitamin D levels in normal pregnancy with second trimester CED pregnancy; know the difference between ferritin in normal pregnancy and second trimester CED pregnancy; know the correlation between vitamin D and ferritin in normal pregnancy and second trimester CED pregnancy; know the correlation between vitamin D and UAC in normal pregnancy and second trimester CED pregnancy. This study used an analytical test (case-control) with randomization of pregnant and pregnant CED patients in the Sukomanunggal district. The results showed that the difference in Vitamin D (33.5380 ± 5.60498 vs 32.4300 ± 4.40708) p = 0.166, the comparison was not significant. The difference in ferritin (17.4080 ± 10.90625 vs 24.7420 ± 21.79586) p = 0.388 comparison was not significant. The correlation between vitamin D and ferritin (p = 0.030) had a significant relationship. There was no significant correlation between Vitamin D and UAC (p = 0.730). The correlation between ferritin and UAC (p = 0.304) was not significant.  Keywords: Vitamin D, Iron, Ferritin, UAC, CEDAbstract: Based on the prevalence of the Kediri Health Office in 2013 and 2014, pregnancy in CED in Kediri was 6.6% and 6.7%, which was an increase of 0.1% from the previous year. According to the prevalence of CED pregnancy in Badas Puskesmas in 2013 and 2014, it was 7.8% and 6.1%. Aimed at knowing the differences in vitamin D levels in normal pregnancy with second trimester CED pregnancy; know the difference between ferritin in normal pregnancy and second trimester CED pregnancy; know the correlation between vitamin D and ferritin in normal pregnancy and second trimester CED pregnancy; know the correlation between vitamin D and UAC in normal pregnancy and second trimester CED pregnancy. This study used an analytical test (case-control) with randomization of pregnant and pregnant CED patients in the Sukomanunggal district. The results showed that the difference in Vitamin D (33.5380 ± 5.60498 vs 32.4300 ± 4.40708) p = 0.166, the comparison was not significant. The difference in ferritin (17.4080 ± 10.90625 vs 24.7420 ± 21.79586) p = 0.388 comparison was not significant. The correlation between vitamin D and ferritin (p = 0.030) had a significant relationship. There was no significant correlation between Vitamin D and UAC (p = 0.730). The correlation between ferritin and UAC (p = 0.304) was not significant.  Keywords: Vitamin D, Iron, Ferritin, UAC, CED